2021
DOI: 10.1556/2060.2021.00187
|View full text |Cite
|
Sign up to set email alerts
|

ARHGEF19 promotes the growth of breast cancer in vitro and in vivo by the MAPK pathway

Abstract: Objective To assess the expression of ARHGEF19 in human breast cancer, investigate its role in breast cancer, and clarify the mechanism. Methods Bioinformatics analysis, immunoblot, quantitative PCR, and immunohistochemical (IHC) assays were performed to assess ARHGEF19 expression in breast cancer. CCK-8 and Edu assays were conducted to reveal its role in breast cancer cell proliferation. Flow cytometry (FCM) assays and immunoblot were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Studies showed that it played an important role in ovarian cancer by affecting cell proliferation and tumour sensitivity to therapy ( 34 ). Furthermore, the ARHGEF19 gene located on chromosome 2 and the LIMCH1 gene located on chromosome 13, within each of which we found one SNP ( TIGRP2P33447_rs8841788 and TIGRP2P176993_rs9197628 , respectively), were associated with an increased risk of breast cancer ( 3 , 30 ).…”
Section: Discussionmentioning
confidence: 84%
“…Studies showed that it played an important role in ovarian cancer by affecting cell proliferation and tumour sensitivity to therapy ( 34 ). Furthermore, the ARHGEF19 gene located on chromosome 2 and the LIMCH1 gene located on chromosome 13, within each of which we found one SNP ( TIGRP2P33447_rs8841788 and TIGRP2P176993_rs9197628 , respectively), were associated with an increased risk of breast cancer ( 3 , 30 ).…”
Section: Discussionmentioning
confidence: 84%